Pug the prince - May, Kyla (New York, NY : Scholastic Inc., 2023)
When Bella wins a poster-making contest at the animal shelter, she gets to be queen of the 'Adopt-an-Animal' parade. That can only mean one thing . . . Bub the pug is her prince! But Bub has no idea what a prince does. Can he figure it out in time to help Bella be the best queen she can be?
1.7
K-3
Keywords: Pug -- Juvenile fiction; Dogs -- Juvenile fiction; Parades -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; Diaries -- Juvenile fiction; Humorous stories; Pug -- Fiction; Dogs -- Fiction; Parades -- Fiction; Human-animal relationships -- Fiction; Diaries -- Fiction; Diary fiction; Animal fiction; Humorous fiction